2010
DOI: 10.1038/jcbfm.2010.115
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of GAD65 has Major Impact on Synaptic GABA Synthesized from Astrocyte-Derived Glutamine

Abstract: c-Aminobutyric acid (GABA) synthesis from glutamate is catalyzed by glutamate decarboxylase (GAD) of which two isoforms, GAD65 and GAD67, have been identified. The GAD65 has repeatedly been shown to be important during intensified synaptic activity. To specifically elucidate the significance of GAD65 for maintenance of the highly compartmentalized intracellular and intercellular GABA homeostasis, GAD65 knockout and corresponding wild-type mice were injected with [1-13 C]glucose and the astrocyte-specific subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 42 publications
3
63
0
Order By: Relevance
“…In line with these findings, we have previously reported that the synthesis of neurotransmitter GABA is altered during chronic HE (Leke et al, 2011a), albeit no change was observed in the expression of GAD65, which is the GAD isoform closely associated with the biosynthesis of GABA in the vesicular neurotransmitter pool Waagepetersen et al, 1999Waagepetersen et al, , 2001Walls et al, 2011). Considering that glutamine is important in the restoration of GABA pools and that synthesis of this amino acid is disturbed during HE, it is possible that during this neurologic disorder the expression of the glutamine transporter isoforms might be altered which would consequently affect the function of the glutamate/GABA-glutamine cycle and thus likely contribute to the observed disturbance of GABA neurotransmitter synthesis (for further discussion, see Walls et al, 2015).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In line with these findings, we have previously reported that the synthesis of neurotransmitter GABA is altered during chronic HE (Leke et al, 2011a), albeit no change was observed in the expression of GAD65, which is the GAD isoform closely associated with the biosynthesis of GABA in the vesicular neurotransmitter pool Waagepetersen et al, 1999Waagepetersen et al, , 2001Walls et al, 2011). Considering that glutamine is important in the restoration of GABA pools and that synthesis of this amino acid is disturbed during HE, it is possible that during this neurologic disorder the expression of the glutamine transporter isoforms might be altered which would consequently affect the function of the glutamate/GABA-glutamine cycle and thus likely contribute to the observed disturbance of GABA neurotransmitter synthesis (for further discussion, see Walls et al, 2015).…”
Section: Discussionsupporting
confidence: 70%
“…In this context it is of interest that using bileduct ligated rats (BDL), an experimental model of chronic HE, it has been demonstrated that the biosynthetic pathway for GABA was altered to occur preferentially via the tricarboxylic acid (TCA) cycle relative to the direct decarboxylation of glutamate not involving the TCA cycle (Leke et al, 2011a). However, no differences in the gene expression were found for the glutamate decarboxylase (GAD) enzyme isoforms GAD65 and GAD67 , which have different roles in the two GABA biosynthetic pathways mentioned earlier (Waagepetersen et al, 1999(Waagepetersen et al, , 2001Walls et al, 2011). Therefore, it can be hypothesized that glutamine transfer between astrocytes and neurons may be altered leading to changes in the biosynthesis of neurotransmitter GABA.…”
Section: Introductionmentioning
confidence: 87%
“…[23][24][25][26] In the present study, the level of cortical Glu (13.8 mmol/g), GABA (2.4 mmol/g), NAA (8.1 mmol/g), and Ins (6.5 mmol/g) is slightly higher than in vivo values, but significantly lower than ex vivo values. 27 Although absolute levels of metabolites are reported to vary across different studies, there seems to be a specific pattern for variation in the level of neurometabolites across the brain. Our data indicate that Glu level decreases in the following order: the cerebral cortex4hippocampus4striatumBthalamus-hypothalamus4 cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…While GAD67 is expressed throughout the cytosol, GAD65 is the dominant presynaptic isoform, which is directly associated to presynaptic vesicles and therefore seems to be important for their filling. 106,155,156 This filling process, however, requires activity of a vacuolar H ĂŸ -ATPase that provides the electrical (DC) and chemical (DpH) components of the driving force for the vesicular inhibitory amino-acid transporter. 147,157 After release to the synaptic cleft, re-uptake of GABA occurs via Na ĂŸ -/Cl À -dependent GABA transporter 1 in the presynaptic terminal or via GAT-3 in processes of astrocytes that enwrap the synapse.…”
Section: Energy Utilization Of Fast-spiking Behavior and Synaptic Inhmentioning
confidence: 99%